Предпосылки формирования рынка объектов интеллектуальной собственности - Лазарева, Е.В.; Крупина, С.В. (Економічні інновації, 2011)
У дослідженні розглянуто основні передумови формування ринку інновацій і його сегмента - ринку об'єктів інтелектуальної власності (ОІВ). Проведено аналіз окремих характеристик, оцінка обсягу цього ринку і ринку високотехнологічних послуг. Запропоновано структуру ринку інновацій, заснована на детермінантах конкурентоспроможності. In research modern the basic preconditions of formation of the market of innovations and his segment – the market of objects of intellectual property (OIP) are considered. The analysis of separate characteristics, an estimation of volume of this market and the market of highly technological services is carried out. The structure of the market of the innovations, based on competitiveness determinants, is offered.